Pemilihan Kriteria Penerima Vaksin Dengan Metode TOPSIS - Sefrika, S (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2021)
The Covid19 pandemic which has been taking place since the beginning of 2020 has paralyzed part of the people's economic life. As a result, many countries have implemented massive social restrictions. One of the solutions provided by the government is by administering vaccines to the Indonesian people. This vaccine is expected to be one of the solutions to prevent the transmission of the Covid19 virus and prevent the risk of spreading Covid19. This research aims to conduct further study of vaccine recipients based on the urgency according to the priority scale by considering the aspects that have been determined by the COVID-19 handling task force. This research uses the TOPSIS method. TOPSIS is a multi-criteria decision-making method based on the concept that the best alternative not only has the shortest distance from the positive ideal solution but also the longest distance from the negative ideal solution. The research resulted in data that the community who should be the priority for the next vaccine recipient is the economy actor society (C2). Furthermore, the values of the two vulnerable communities in social, economic and social aspects and finally public officers (C3). The research resulted in data that the people who should be the priority for the next vaccine recipients are the people who are economic actors (C2).